DIMENSI PENILAIAN DALAM PEMBELAJARAN BAHASA ARAB PADA EMPAT KETERAMPILAN BERBAHASA - Muslimin Resi; Herdah (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This study aims to analyze the concepts, characteristics, principles, and dimensions of assessment in Arabic language learning, particularly in the four language skills: listening, speaking, reading, and writing. The study employed a qualitative approach using a library research design that focused on conceptual analysis of various academic literature relevant to language assessment. The data were collected through documentation techniques from books, scientific journal articles, and academic publications related to the evaluation of Arabic language learning. The data were then analyzed using content analysis to identify, classify, and synthesize various concepts related to language assessment practices. The findings reveal that assessment in Arabic language learning should be authentic, contextual, and oriented toward communicative competence, while integrating linguistic elements with language skills. In addition, assessment should be conducted based on the principles of validity, reliability, objectivity, practicality, transparency, fairness, and sustainability. The novelty of this study lies in its comprehensive explanation of the assessment dimensions across the four Arabic language skills, along with their indicators and assessment techniques. These findings provide implications for educators in designing Arabic language assessments that are more systematic, communicative, and relevant to language learning objectives.